ANALISIS KINERJA SIMPANG TAK BERSINYAL PADA JALAN SIMPANG HOTEL SANTIKA PREMIER KOTA AMBON - Sani Sahertian; Anthoneta Maittimu; Penina T. Istia (Journal Agregate, 2022)
The unsignalized intersection on the Jln. Clove Gardens, Jln. Jendral Sudirman, and Jln. Galunggung is an asymmetrical intersection which is currently experiencing problems. This intersection is the only connecting road from within the city to outside the city, or vice versa and is the main link where vehicles meet from the clove garden road, Jendral Sudirman road and Galunggung road sections. This intersection has a busy traffic activity where you can see many types of vehicles ranging from motorcycles, light vehicles, heavy vehicles to pedestrians passing through the intersection. And there are activities at the intersection approach such as public transportation that stops to raise or lower passengers and vehicles that enter and leave beside the road from the environment around the intersection. The purpose of this research is to overcome traffic flow conflicts at the unsignalized intersection, this research takes place at the unsignalized intersection Jln. Clove Gardens, Jln. Jendral Sudirman, and Jln. Galunggung Ambon City, using primary data and secondary data, as well as data sources obtained from survey results, and analysis method used PKJI 1997 analysis. The results obtained are traffic performance at the unsignalized intersection of Jln. Clove Gardens, Jln. Jendral Sudirman, and Jln. Galunggung got the highest density level on Saturday, September 4, 2021 with a value of Capacity (C) = 2275 pcu/hour, traffic flow (Q) = 4879 pcu/hour, and Degree of Saturation (DS) > 2,14 in 17 time period: 00 – 18:00. The speed of light vehicles that pass Jln. Jenderal Sudirman is 9.05 km/hour which occurs in the period 17:00 – 18:00.Keywords: unsignalized intersection, hotel santika road